Exercise in patients with acetabular retroversion and excessive anterior pelvic tilt: A feasibility and intervention study. (October 2022) - Falk Brekke, Anders; Overgaard, Søren; Mussmann, Bo; Poulsen, Erik; Holsgaard-Larsen, Anders
Abstract: Background: Acetabular retroversion is associated with femoroacetabular impingement syndrome (FAIS). Anterior pelvic tilt enhances risk of FAIS. Objectives: To investigate feasibility and change in patient-reported symptoms of a home-based exercise intervention in patients with acetabular retroversion and excessive anterior pelvic tilt, in comparison with a prior control period. Design: Prospective intervention study. Methods: Patients (18–40 years) not eligible for surgery, with radiographic signs of acetabular retroversion and excessive anterior pelvic tilt were recruited. An 8-week control period was followed by an 8-week training period. The home-based intervention consisted of education and exercises for core stability, muscle strengthening and stretching for reducing anterior pelvic tilt. Feasibility assessments were dropout (≤10%), adherence (≥75% of sessions), exercise-related pain, and adverse events. Primary outcome was change in the Copenhagen Hip and Groin Outcome Score (HAGOS) pain-subscale. Pelvic tilt was measured by EOS scanning. Results: Forty-two patients (93% female, mean age 22.2 ± 4.2 years) were included. Dropout rate was 7% and satisfactory adherence was demonstrated by 85%. Exercise-related pain and adverse events were acceptable. Between-period mean change score for HAGOS-PAIN was 5.2 points (95% CI: −0.3–10.6) and −1.6° (95% CI: −3.9–0.7) of anterior pelvic tilt. Patients responding positively (≥10 points) (n = 10, 26%), had pre-exercise moderate pain (HAGOS-PAIN 47.5–70 points). Conclusions: Current exercise intervention was feasible. However, we found no clinically relevant changes in self-reported hip-related pain or anterior pelvic tilt. Post hoc responder analysis revealed that patients with moderate pain at baseline might benefit from this exercise. Highlights: Exercise targeting anterior pelvic tilt in patients with acetabular retroversion was feasible. Patients with acetabular retroversion and moderate hip-related pain may benefit from exercise. Anterior pelvic tilt may be considered in future interventions in patients with FAIS.